Physiologic parameters in female Red-billed curassows (Crax blumenbachii) in rehabilitation - Marietto-Gonçalves, Guilherme A. [UNESP]; Martins, Mayra T.A. [UNESP]; Souza, Katiane L. [UNESP]; Takahira, Regina K. [UNESP]; Gonçalves, Roberto C. [UNESP]; Andreatti Filho, Raphael L. [UNESP] (FapUNIFESP (SciELO), 2016)
The present paper reports blood gas analysis, hematologic and micro bacteriologic information on four female Red-billed curassows, rescued from illegal wild animal trading, that were undergoing habilitation for reintroduction into the wild through Projeto Centrofauna/Botucatu-SP. There is a lack of physiological data on this species, endemic to the region of Atlantic Forest (Mata Atlântica), now under threat of extinction. This lack of information makes the clinical evaluation of these birds very difficult and has a direct and adverse effect on any of these birds received for medical treatment in hospitals, veterinary clinics and centers for research and conservation, as well as in reintroduction centers.
Keywords: Animal health; Cloacal microbiota; Crax blumenbachii; Physiological parameters; Red-billed curassow